2015
DOI: 10.7737/msfe.2015.21.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Min-Max Regret Version of an m-Machine Ordered Flow Shop with Uncertain Processing Times

Abstract: We consider an m-machine flow shop scheduling problem to minimize the latest completion time, where processing times are uncertain. Processing time uncertainty is described through a finite set of processing time vectors. The objective is to minimize maximum deviation from optimality for all scenarios. Since this problem is known to be NPhard, we consider it with an ordered property. We discuss optimality properties and develop a pseudo-polynomial time approach for the problem with a fixed number of machines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They showed that only one case is polynomially solvable and the other two cases are NP-hard. Park and Choi (2015) considered uncertain processing times in the m-machine flow shop scheduling problem. Since the general problem with the objective function of minimizing the maximum deviation from the optimality for all scenarios is proved to be NP-hard (Kouvelis and Daniels, 2000), they studied the problem with ordered processing times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that only one case is polynomially solvable and the other two cases are NP-hard. Park and Choi (2015) considered uncertain processing times in the m-machine flow shop scheduling problem. Since the general problem with the objective function of minimizing the maximum deviation from the optimality for all scenarios is proved to be NP-hard (Kouvelis and Daniels, 2000), they studied the problem with ordered processing times.…”
Section: Literature Reviewmentioning
confidence: 99%